catena-Poly[[(1,10-phenanthroline-κ(2) N,N')copper(II)]-μ-2,2'-iminodibenzoato-κ(4) O,O':O'',O'''] - Yuste-Vivas, Consuelo (2013)
The structure of the title compound, [Cu(C14H9NO4)(C12H8N2)] n , consists of zigzag polymeric chains along the c axis. The asymmetric unit contains one Cu(II) atom which is coordinated by one 2,2'-imino-dibenzoate ligand and a one phenanthroline unit. Two intra-molecular N-H⋯O hydrogen bonds occur. The supra-molecular structure is characterized by weak C-H⋯O hydrogen bonds and π-π stacking inter-actions, forming a three-dimensional supramolecular network. The shortest centroid-centroid distances between neighbouring phenanthroline aromatic rings and 2,2'-imino-dibenzoate rings are 3.684 (1) and 3.640 Å, respectively. The shortest intra-chain Cu⋯Cu distance is 7.2885 (9) and the shortest Cu⋯Cu distance between Cu atoms in different chains is 7.1103 (6) Å.